1972
DOI: 10.1159/000180161
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Status in Chronic Uraemic Patients

Abstract: Magnesium level in bone, skeletal muscle, the erythrocyte, serum and serum ultrafiltrate were estimated in ten patients with advanced uraemia. Eight patients were found to have significantly low skeletal muscle magnesium, indicating significant deficit of the cation. However, there was no correlation between skeletal muscle magnesium and magnesium levels of the other tissues. Bone magnesium was normal in all patients as was erythrocyte magnesium. Serum magnesium level was variable, but 6 of the 8 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1974
1974
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…In studies of human necropsy material, decreased bone carbonate (19), Ca/P ratio (19,20), and decreased bone density (19) have been reported. Since the advent of atomic absorption, increased Mg has been reported in necropsy material (21,22), but contrary to our findings, normal Mg has been reported in biopsy material (23).…”
Section: Methodscontrasting
confidence: 99%
“…In studies of human necropsy material, decreased bone carbonate (19), Ca/P ratio (19,20), and decreased bone density (19) have been reported. Since the advent of atomic absorption, increased Mg has been reported in necropsy material (21,22), but contrary to our findings, normal Mg has been reported in biopsy material (23).…”
Section: Methodscontrasting
confidence: 99%
“…Contiguglia et al [50] also found a 66% increase in bone magnesium in patients with chronic renal failure. An increase in bone magnesium in uremia was also noted by Berlyne et al [51], but not by Lim and Jacob [52]. The latter study is the only one documenting normal bone magnesium; this study, it should be pointed out, was carried out in the Far East.…”
Section: Magnesium and Bone Diseasesupporting
confidence: 54%
“…In patients with chronic renal failure (and also in normal subjects), tra becular bone magnesium content was significantly grea ter than cortical magnesium content. However, some studies have found no difference in magnesium content compared to normal values [61][62][63]. Patients with uremia of more than 1 year duration and dialysis patient have been reported to have significantly elevated bone magne sium [62], In such patients, magnesium content correlated with osteoid area, and changes in magnesium were di rectly proportional to changes in H P 04 and inversely related to excess calcium in bone powder.…”
Section: Magnesium and Bone Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Liver magnesium was significantly reduced after 62 days of feeding magnesium deficient diet to rats [20]. Lim and Jacobs [21][22][23] have suggested that muscle magnesium is the most freely exchangeable and thus the first to fall during magnesium depletion. An increase in the magnesium content of kidney in magnesium deficient animals may be due to the increased reabsorption of magnesium by the loop of Henle during magnesium deficiency as it is the major site of magnesium re-absorption in the renal tubule and principal locus of renal control of magnesium excretion [24].…”
Section: Discussionmentioning
confidence: 99%